2009
DOI: 10.2478/s11756-009-0193-5
|View full text |Cite
|
Sign up to set email alerts
|

Some possibilities of representing microcirculation in human spleen

Abstract: The representation of microcirculation can be approached in several ways. One of the possibilities is to represent the endothelium (endothelial or sinus lining cells) and their basement membrane on the basis of detecting the known components and the expression of the surface antigenes by the methods of immuno-, enzyme-or lectino-histochemical analysis, or by staining or impregnation histological methods. The other possibility is the examination of samples by transmission and scanning electron microscopy. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The ultrathin sections were contrasted with uranyl acetate and lead citrate. For SEM we identically postfixed the tissue, after dehydration we dried it at the critical point of CO2 (CPD 020 Balzers Union) and galvanized it with gold for 2.5 min at the pressure of 2500 Pa and the current of 50 mA in the apparatus SCD 030 Balzers Union, the anode-cathode distance being 55 mm Gálfiová et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…The ultrathin sections were contrasted with uranyl acetate and lead citrate. For SEM we identically postfixed the tissue, after dehydration we dried it at the critical point of CO2 (CPD 020 Balzers Union) and galvanized it with gold for 2.5 min at the pressure of 2500 Pa and the current of 50 mA in the apparatus SCD 030 Balzers Union, the anode-cathode distance being 55 mm Gálfiová et al 2009). …”
Section: Methodsmentioning
confidence: 99%
“…We note that as the primary deformation mode is bending and that since the maximum bending deflection would scale as L 3 EC /D 4 EC , the expected EC deflections would be comparable to those with the somewhat uncertain "averages" of LEC ∼ 9µm and DEC ∼ 1.8 − 2µm. We also note the sinus image of Gálifiová et al [39] in Fig. 1e that suggested that the EC length may be larger than the erstwhile estimated average of 9µm.…”
Section: Model and Simulation Detailsmentioning
confidence: 54%
“…1c and suggested by Fig. 1e taken from Gálfiová et al [39]. Drenckhahn and Wagner [35] report spacings, based on optical microscopy, of individual ring fibers in the human spleen in the range 4 − 5µm (see their Figs.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
See 1 more Smart Citation
“…The blood elements with undisturbed elasticity of cell membrane subsequently return to the blood circulation by penetrating through the small openings in the walls of specialized capillaries (splenic venous sinuses) (ref. [7][8][9][10] ). The altered erythrocytes in hereditary spherocytosis are vulnerable to splenic sequestration and subsequent lysis and cause the characteristics of this disease such as jaundice, anemia, splenomegaly, and cholelithiasis.…”
Section: Introductionmentioning
confidence: 99%